Representações sociais das religiões afro-brasileiras: o que pensam os estudantes das escolas estaduais de referência da cidade do Recife - Melo, Constantino Jose Bezerra de (2015)
This thesis is related to the master of religious studies, the research line: Brazilian religious field, culture and society. It aims to analyze the social representations of african-Brazilian religions, presented by students from three schools of the State Public Reference Network of Pernambuco, located in the northern region of the city of Recife. The african-Brazilian religions were historically generated in coping with the Portuguese colonizers and slave process, resulting in a process of reworking and reinterpretation as a religious outlet for preservation of minority religions of blacks and natives. To historically contextualize the african-Brazilian religions, used as bibliographical research, the production of knowledge of history, anthropology, sociology and social psychology, to understand how these religions were designed in the past and re-signified in this. This is a field research, qualitative and descriptive. Thus, data collection was conducted through emistructured interviews, applied to eighteen respondents to be analyzed what students think about the african-Brazilian religions as well as the three coordinators of the three schools in order to examine the performance of actions recommended by law 10.639/2003, which deals with the history and Afro-Brazilian Culture, indicating a work of deconstruction and combating ethnic and racial and religious prejudice. The data analysis was performed by analyzing discourse. As a result, it is expected to problematize the approach of african-Brazilian religions represented by students from state school in Pernambuco, expanding the program Integral Education of Pernambuco valuing education in religious and spiritual dimension, strengthening the concept of education critical and emancipatory stereotypes, prejudice and religious discrimination, and thereby enable building of a more just and democratic society, where diversity and interreligious dialogue can be respected.